Non-aqueous electrolyte additive for Prussian blue and analogues thereof, electrolyte and sodium ion battery

By adding silane electrolyte additives to the electrolyte of Prussian blue positive electrode material, the negative impact of water molecules and HF in the electrolyte on battery performance is solved, and the cycle stability and capacity utilization of the battery are significantly improved.

CN119495819APending Publication Date: 2025-02-21ZHEJIANG NATRIUM ENERGY CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202311058556.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-21
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

In practical applications, Prussian blue cathode materials have problems such as low capacity utilization, difference in magnification and unstable circulation. The main reason is related to the Fe(CN)6 vacancy and lattice water molecules in their structure, resulting in a decrease in electrochemical sodium storage performance. .

Method used

A non-aqueous electrolyte additive, including silane additives, contains compounds with Si-O structure and Si-N structure. By reacting these compounds with water molecules and HF in the electrolyte, the electrolyte is reduced. The concentration of water molecules and HF is improved, thereby improving battery performance.

Benefits of technology

Effectively remove water molecules and HF in the electrolyte, improve the cycle stability and capacity utilization of the battery, and extend the cycle life of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119495819A_ABST
    Figure CN119495819A_ABST
Patent Text Reader

Abstract

The invention discloses a non-aqueous electrolyte additive for Prussian blue and analogues thereof, an electrolyte and a sodium-ion battery, and relates to the technical field of sodium-ion batteries, the non-aqueous electrolyte additive comprises a silane additive, the silane additive comprises a compound with a Si-O structure or / and a compound with a Si-N structure, in the silane additive, the silane additive comprises a compound with a Si-O structure and / or a compound with a Si-N structure, the mass ratio of the compound with the Si-O structure to the compound with the Si-N structure is (10: 0)-(0: 10), the mass percentage content of the electrolyte additive in the electrolyte is 0.5-10%, and compared with a contrast sample without the electrolyte additive, the electrolyte and the sodium ion battery prepared by using the electrolyte additive provided by the invention have the advantages that the charge-discharge rate of the contrast sample is 1C, the charge-discharge rate of the sodium ion battery is greatly improved, and the charge-discharge rate of the sodium ion battery is greatly improved. The first charge-discharge capacity and the cycle performance are obviously improved, and the capacity retention ratio is still 90% or above after 200 cycles.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of sodium ion batteries, and in particular to a non-aqueous electrolyte additive for Prussian blue and its analogs, an electrolyte and a sodium ion battery. Background Art

[0002] The sodium element required for sodium-ion batteries is abundant, accounting for 2.36% of the elements in the earth's crust. Compared with lithium-ion batteries, sodium-ion batteries have the advantage of low cost. According to data from China Science and Technology Haina, the cost of sodium-ion batteries can be reduced by 30% to 40% compared with lithium-ion batteries. Therefore, even though sodium-ion batteries are slightly lower in energy density than lithium-ion batteries that have been commercially applied, they can still occupy a place in large-scale energy storage applications and low-speed electric vehicles.

[0003] Prussian blue cathode materials are one of the three major cathode materials for sodium ion batteries. They are widely studied and applied because of their open three-dimensional channels, high theoretical capacity, simple synthesis, low preparation cost, good structural stability and rate performance. However, in practical applications, they generally have disadvantages such as low capacity utilization, poor rate and unstable cycle. The main reason may be related to the Fe(CN)6 vacancies and lattice water molecules in the Prussian blue structure. These Fe(CN)6 vacancies and water molecules will seriously affect the electrochemical sodium storage performance of Prussian blue, specifically: 1. Fe(CN)6 vacancies reduce the redox active center and reduce the Na content in the lattice, resulting in a decrease in the actual sodium storage capacity; 2. Fe(CN)6 vacancies increase the water content in the lattice, and some water molecules will escape into the electrolyte, resulting in a decrease in the first cycle efficiency and cycle efficiency; 3. Fe(CN)6 vacancies destroy the integrity of the lattice, and Na easily causes lattice distortion and structural collapse when it escapes / embeds, resulting in serious attenuation of cycle performance. 4. The presence of water molecules will cause a series of decompositions of NaPF6 in the electrolyte (Equation 1-5), generating substances such as HF. HF will intensify the dissolution of the active metal component Mn in the Prussian blue material, further leading to the instability of the positive electrode material structure, and catalyzing the decomposition of the negative electrode SEI, resulting in a decrease in battery performance. Therefore, it is particularly important to develop electrolyte additives that match the material's own characteristics, especially electrolyte additives that remove water and acid.

[0004]

[0005] PF5+H2O→POF3+HF (2)

[0006] POF3+H2O→PO2F 2- +HF (3)

[0007] PO2F 2- +H2O→PO3F 2-+HF (4)

[0008] PO3F 2- +H2O→PO4 3- +HF (5) Summary of the invention

[0009] The first aspect of the present invention aims to provide a non-aqueous electrolyte additive for Prussian blue and its analogs, which can remove water molecules and HF in the electrolyte and the by-products will not affect the battery performance, so as to solve the problem of poor cycle performance of Prussian blue positive electrode materials.

[0010] The technical solution adopted by the present invention is as follows:

[0011] A non-aqueous electrolyte additive for Prussian blue and its analogs, comprising a silane additive, wherein the silane additive comprises a compound with a Si-O structure or / and a compound with a Si-N structure, and in the silane additive, the mass ratio of the compound with a Si-O structure to the compound with a Si-N structure is 10:0 to 0:10.

[0012] Further:

[0013] The compound having a Si-O structure is selected from any one or more of N,O-bis(trimethylsilyl)trifluoroacetamide, dimethoxydimethylsilane, (2-allylphenoxy)trimethylsilane, diphenyldimethoxysilane, hexamethyldisiloxane, allyltrimethoxysilane, vinyldimethylethoxysilane, methylphenyldimethoxysilane, methylvinyldimethoxysilane, diethoxydiphenylsilane, and phenyltrimethoxysilane.

[0014] The compound having a Si-N structure is selected from any one or more of heptamethyldisilazane, 3-trimethylsilyl-2-oxazolidinone, hexamethyldisilazane, trimethylsilyldiethylamine, hexamethylcyclotrisilazane, N-allylhexamethyldisilazane, ethylhexamethyldisilazane, and trimethylsilyl isocyanate.

[0015] In the silane additive, the mass ratio of the Si-O structure compound to the Si-N structure compound is 10:0 to 5:5.

[0016] Further:

[0017] A non-aqueous electrolyte additive for Prussian blue and its analogs, further comprising a film-forming additive, the mass percentage of which is as follows:

[0018] Silane additives 40~90%

[0019] Film-forming additives 10-60%

[0020] The film-forming additive is selected from any one or more of fluoroethylene carbonate (FEC), vinylene carbonate (VC), propenyl-1,3-sultone (PST), and dithiothreitol (DTD).

[0021] The second aspect of the present invention provides an electrolyte comprising the following composition by mass percentage:

[0022] Electrolyte main salt 4.5%~24.5%

[0023] Non-aqueous electrolyte additives 0.5% to 10%

[0024] Organic solvent 75%~95%.

[0025] Further:

[0026] The main salt of the electrolyte is a sodium salt, selected from one or more of sodium hexafluorophosphate (NaPF6), sodium tetrafluoroborate (NaBF4), sodium perchlorate (NaClO4) and sodium trifluoromethanesulfonate (NaOTf). Preferably, the main salt of the electrolyte is sodium hexafluorophosphate, and the mass percentage content in the electrolyte is 12% to 15%.

[0027] The organic solvent comprises chain carbonate and cyclic carbonate, and the mass ratio of the chain carbonate to the cyclic carbonate is 3:7 to 8:2.

[0028] The cyclic carbonate is selected from one or two of ethylene carbonate (EC), propylene carbonate (PC) and butylene carbonate (BC).

[0029] The chain carbonate is selected from one or more of dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), and methyl propyl carbonate (MPC).

[0030] The mass content of the organic solvent in the electrolyte is preferably 78% to 92%.

[0031] The mass content of the non-aqueous electrolyte additive in the electrolyte is preferably 1.5-5.0%.

[0032] The non-aqueous electrolyte additive includes a compound with a Si-O structure and / or a compound with a Si-N structure.

[0033] Preferably, in the silane additive, the mass ratio of the compound having a Si-O structure to the compound having a Si-N structure is 10:0 to 5:5.

[0034] The compound having a Si-O structure is selected from any one or more of N,O-bis(trimethylsilyl)trifluoroacetamide, dimethoxydimethylsilane, (2-allylphenoxy)trimethylsilane, diphenyldimethoxysilane, hexamethyldisiloxane, allyltrimethoxysilane, vinyldimethylethoxysilane, methylphenyldimethoxysilane, methylvinyldimethoxysilane, diethoxydiphenylsilane, and phenyltrimethoxysilane.

[0035] The compound having a Si-N structure is selected from any one or more of heptamethyldisilazane, 3-trimethylsilyl-2-oxazolidinone, hexamethyldisilazane, trimethylsilyldiethylamine, hexamethylcyclotrisilazane, N-allylhexamethyldisilazane, ethylhexamethyldisilazane, and trimethylsilyl isocyanate.

[0036] The third aspect of the present invention is to provide a sodium ion battery, comprising a positive electrode, a negative electrode and an electrolyte, wherein: the positive electrode is made of a Prussian blue material, the negative electrode is made of a metallic sodium sheet, and the electrolyte is the electrolyte described above in the present invention.

[0037] The mechanism of action of the electrolyte additive in the present invention is as follows:

[0038] The non-aqueous electrolyte additive in the present invention is a silane additive, which can exist stably in the electrolyte and does not cause side reactions with the organic solvent and the main salt of the electrolyte.

[0039] When sodium hexafluorophosphate is selected as the main salt of the electrolyte, sodium hexafluorophosphate will decompose into HF when it encounters water molecules in the Prussian blue material. The Si in the silane additive has a high affinity for F and can form a Si-F structure with HF to protect the positive electrode material and the negative electrode SEI film from corrosion.

[0040] When the main salt of the electrolyte is a sodium salt other than sodium hexafluorophosphate, no HF is generated. Silane additives react with water molecules released by Prussian blue materials to generate NH products and -(Si-O)n- polymer salts, thereby reducing the water molecule content in the electrolyte.

[0041] In summary, the non-aqueous electrolyte additive of the present invention can react with water molecules and HF to reduce the concentration of water molecules and HF in the electrolyte, thereby achieving the effect of improving battery capacity and cycle.

[0042] The beneficial effects of the present invention are as follows:

[0043] (1) The present invention can effectively remove water molecules in the electrolyte.

[0044] There are three types of water in Prussian blue materials: free water, interstitial water and bound water. Among these three types of water, bound water exists in the internal structure of Prussian blue materials and is difficult to remove. It can be used as hydrated sodium ions ([Na(H2O) n ] + ) in the form of hydrated sodium ions. If not removed in time, the bound water will still be embedded in the positive electrode material in the form of hydrated sodium ions. Such a large volume of intercalation will inevitably lead to the collapse of the positive electrode material structure and the decrease of capacity. The silane additive of the present invention can greatly improve the problem of positive electrode material structure collapse due to its water removal effect.

[0045] (2) The present invention can effectively remove HF in the electrolyte.

[0046] When sodium hexafluorophosphate is selected as the main salt of the electrolyte, sodium hexafluorophosphate will decompose into HF when it encounters water molecules in the Prussian blue material. The Si in the silane additive has a high affinity for F and can form a Si-F structure with HF to protect the positive electrode material and the negative electrode SEI film from corrosion.

[0047] (3) In summary, the non-aqueous electrolyte additive in the present invention can largely suppress the adverse effects of water molecules and HF in the electrolyte on the battery's electrical performance, and can significantly improve the battery capacity and cycle life.

[0048] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0049] Figure 1 The figure is a comparison of the battery performance curves of a battery prepared using the electrolyte of Example 1 and an electrolyte without adding additives. DETAILED DESCRIPTION

[0050] Example 1

[0051] (1) Preparation of electrolyte

[0052] Electrolyte formula:

[0053]

[0054] Preparation method: Ethylene carbonate, propylene carbonate and diethyl carbonate are mixed evenly according to the formula ratio, and the main salt sodium hexafluorophosphate and electrolyte additives fluoroethylene carbonate and (2-allylphenoxy)trimethylsilane are added in the above amount and mixed evenly to obtain sodium hexafluorophosphate electrolyte.

[0055] (2) Preparation of sodium ion batteries

[0056] The positive electrode uses a Prussian blue positive electrode material, the negative electrode uses a metal sodium sheet, and the above-mentioned electrolyte is used to assemble a CR2016 button battery, in which the rate and cycle performance tests are carried out at a voltage of 2-4V.

[0057] Comparative Example 1

[0058] The preparation method is the same as that of Example 1, except that no silane additive (2-allylphenoxy)trimethylsilane is added to the electrolyte.

[0059] Performance Test:

[0060] The electrolytes prepared in Example 1 and Comparative Example 1 were assembled into batteries according to the above method and performance tests were performed for comparison. The results are as follows: Figure 1 As shown: when the charge and discharge rate is 1C, after adding the additive provided by the present invention, the cycle stability can be greatly improved. After 200 cycles, the cycle capacity retention rate is improved from 82.89% to 92.14%, an increase of 9.25%.

[0061] Example 2-35: Effects of different silane additive compositions and dosages on battery performance

[0062] The formula and preparation method are the same as those in Example 1, except that the composition and amount of the silane additive in step (1) are adjusted to test the effect on the battery performance, as shown in Table 1.

[0063] Table 1

[0064]

[0065]

[0066]

[0067]

[0068] As shown in Table 1:

[0069] By comparing Example 1 with Examples 2-33, it can be found that the selection of different silane additives has a great influence on the battery performance. Compared with the use of a single silane, Example 33 has the best effect when a mixed silane additive of heptamethyldisilazane, 3-trimethylsilyl-2-oxazolidinone and (2-allylphenoxy)trimethylsilane is used.

[0070] By comparing Example 1 with Examples 34-35, it can be found that in the electrolyte additives, the ratio of film-forming additives to silane additives has a great influence on the battery performance. The best embodiment is that the effect is best when the ratio of film-forming additives to silane additives is 2:3.

[0071] Examples 36-40: Effects of different film-forming additives on battery performance

[0072] The formula and preparation method are the same as those in Example 1, except that the selection of the film-forming additive in step (1) and its ratio with the silane additive are adjusted, and their effects on the battery performance are tested, as shown in Table 2.

[0073] Table 2

[0074]

[0075]

[0076] As shown in Table 2:

[0077] By comparing Example 1 with Examples 36-38, it can be found that different film-forming additives have a great influence on battery performance, and the effect is best when fluoroethylene carbonate is used as the film-forming additive.

[0078] By comparing Example 1 with Examples 39-40, it can be found that the total amount of electrolyte additives has a great influence on battery performance. The electrolyte additives are optimal when their mass content in the entire electrolyte is about 5%. As the amount of electrolyte additives increases, electrode by-products increase and cycle performance deteriorates.

[0079] Examples 41-45: Effects of different electrolyte main salt selections on battery performance

[0080] The formula and preparation method are the same as those in Example 1, except that the selection and dosage of the main salt of the electrolyte in step (1) are adjusted, and the effect on the battery performance is tested, as shown in Table 3.

[0081] Table 3

[0082]

[0083] As shown in Table 3:

[0084] By comparing Example 1 with Examples 41-43, it can be found that the optimal amount of the main salt of the electrolyte is 10% to 25% by mass of the entire electrolyte. As the amount of the main salt in the electrolyte increases, the cycle performance of the battery improves. When the amount of the main salt increases to more than 16.8g, it basically tends to be stable. Considering the material cost, a main salt amount of 16.8g is a better choice.

[0085] By comparing Example 1 with Examples 44-45, it can be found that different selections of the main salt of the electrolyte have a great influence on the battery performance. The best embodiment is sodium hexafluorophosphate, with an amount of 13.68% of the mass content of the entire electrolyte.

[0086] Examples 46-49: Effects of different organic solvents on battery performance

[0087] The formula and preparation method are the same as those in Example 1, except that the selection and amount of the organic solvent in step (1) are adjusted, and the effect on the battery performance is tested, as shown in Table 4.

[0088] Table 4

[0089]

[0090] As shown in Table 4:

[0091] By comparing Example 1 with Examples 46-47, it can be found that the selection of different organic solvents has a great influence on the battery performance, and the best embodiment is a combination of ethylene carbonate, propylene carbonate and ethyl methyl carbonate.

[0092] By comparing Example 1 with Examples 48-49, it can be found that the amount of organic solvent used has a great influence on the battery performance. The best embodiment is: the amount of organic solvent is controlled to 75% to 95% of the mass content of the entire electrolyte, and the best is 81.4%.

Claims

1. A non-aqueous electrolyte additive for Prussian blue and its analogs, characterized in that: The invention comprises a silane additive, wherein the silane additive comprises a compound having a Si-O structure or / and a compound having a Si-N structure. In the silane additive, the mass ratio of the Si-O structure compound to the Si-N structure compound is 10:0 to 0:

10.

2. The non-aqueous electrolyte additive for Prussian blue and its analogs according to claim 1, characterized in that: The compound having a Si-O structure is selected from any one or more of N,O-bis(trimethylsilyl)trifluoroacetamide, dimethoxydimethylsilane, (2-allylphenoxy)trimethylsilane, diphenyldimethoxysilane, hexamethyldisiloxane, allyltrimethoxysilane, vinyldimethylethoxysilane, methylphenyldimethoxysilane, methylvinyldimethoxysilane, diethoxydiphenylsilane, and phenyltrimethoxysilane.

3. The non-aqueous electrolyte additive for Prussian blue and its analogs according to claim 1, characterized in that: The compound having a Si-N structure is selected from any one or more of heptamethyldisilazane, 3-trimethylsilyl-2-oxazolidinone, hexamethyldisilazane, trimethylsilyldiethylamine, hexamethylcyclotrisilazane, N-allylhexamethyldisilazane, ethylhexamethyldisilazane, and trimethylsilyl isocyanate.

4. The non-aqueous electrolyte additive for Prussian blue and its analogs according to claim 1, characterized in that: In the silane additive, the mass ratio of the Si-O structure compound to the Si-N structure compound is 10:0 to 5:

5.

5. The non-aqueous electrolyte additive for Prussian blue and its analogs according to claim 1, characterized in that: The non-aqueous electrolyte additive also includes a film-forming additive, and the mass percentage of the non-aqueous electrolyte additive is as follows: Silane additives 40~90% Film-forming additives 10-60% The film-forming additive is selected from any one or more of fluoroethylene carbonate, vinylene carbonate, propenyl-1,3-sultone, and vinyl sulfate.

6. An electrolyte, characterized in that: It includes the following components by mass percentage: Electrolyte main salt 4.5%~24.5% Non-aqueous electrolyte additives 0.5% to 10% Organic solvent 75%~95% The non-aqueous electrolyte additive includes a silane additive, and the silane additive includes a compound with a Si-O structure and / or a compound with a Si-N structure. In the silane additive, the mass ratio of the Si-O structure compound to the Si-N structure compound is 10:0 to 0:

10.

7. An electrolyte according to claim 6, characterized in that: The main salt of the electrolyte is a sodium salt selected from one or more of sodium hexafluorophosphate, sodium tetrafluoroborate, sodium perchlorate and sodium trifluoromethanesulfonate. The mass percentage of the main salt of the electrolyte in the electrolyte is 12% to 15%.

8. An electrolyte according to claim 6, characterized in that: The organic solvent comprises a chain carbonate and a cyclic carbonate, the mass ratio of the chain carbonate to the cyclic carbonate is 3:7 to 8:2, the cyclic carbonate is selected from one or two of ethylene carbonate, propylene carbonate and butylene carbonate; the chain carbonate is selected from one or more of dimethyl carbonate, diethyl carbonate, ethyl methyl carbonate and methyl propyl carbonate; the mass content of the organic solvent in the electrolyte is 78% to 92%.

9. An electrolyte according to claim 6, characterized in that: The mass content of the non-aqueous electrolyte additive in the electrolyte is 1.5-5.0%, and the non-aqueous electrolyte additive includes a compound with a Si-O structure or / and a compound with a Si-N structure; in the silane additive, the mass ratio of the Si-O structure to the Si-N structure is 10:0-5:5; the compound with the Si-O structure is selected from N,O-bis(trimethylsilyl)trifluoroacetamide, dimethoxydimethylsilane, (2-allylphenoxy)trimethylsilane, diphenyldimethoxysilane, hexamethyldisilazane The compound having the Si-N structure is selected from any one or more of heptamethyldisilazane, 3-trimethylsilyl-2-oxazolidinone, hexamethyldisilazane, trimethylsilyldiethylamine, hexamethylcyclotrisilazane, N-allylhexamethyldisilazane, ethylhexamethyldisilazane and trimethylsilyl isocyanate.

10. A sodium ion battery comprising a positive electrode, a negative electrode and an electrolyte, characterized in that: The positive electrode adopts Prussian blue material, the negative electrode adopts metal sodium sheet, and the electrolyte adopts the electrolyte described in claim 6.

Citation Information

Cited By

  • Aza-silane electrolyte additive, electrolyte and lithium ion battery

    CN120073072A

  • Electrolyte additive, high-temperature stable electrolyte and lithium ion battery

    CN122608652A